Microsatellite instability and hMLH1 and hMSH2 gene expression in postmenopausal women with endometrial cancer - Kulig, Andrzej; Smolarz, Beata; Kozłowska, Elżbieta; Dec, Grażyna; Romanowicz-Makowska, Hanna; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Purpose: Endometrial cancer is one of the most common malignant neoplasms which appear in the uterine body. Endometrial tumorigenesis is still poorly understood. Microsatellite instability (MSI) and hMLH1 and hMSH2 gene expression have been shown in patients from groups with a high risk of endometrial cancer. The paper presents a review of the results of studies showing that alterations in the mismatch repair gene hMLH1 and hMSH2 seem to be important for the development of MSI in these tumors. Materials and methods: The patients diagnosed with endometrial carcinoma have been studied. The microsatellite instability was detected using PCR-SSCP reaction. Results and conclusion: Microsatellite instability seems to be important in the development of various human cancers including endometrial cancer.